Оброблення зображень у безпілотних пристроях - Макаров, Д. С. (ХНУРЕ, 2024)
In recent years, the integration of image processing techniques in unmanned aerial vehicles (UAVs) and autonomous systems has become increasingly vital. This report delves into the multifaceted applications of image processing in enhancing the capabilities of unmanned devices. The exploration includes an overview of contemporary methods, the role of computer vision technologies, and practical implementations in autonomous navigation, obstacle detection, and scene perception. The report also addresses the challenges and prospects in this field. By synergizing image processing with other sensor data, the presentation emphasizes the comprehensive perception achieved by these devices. The conclusion highlights key findings and outlines future research directions
Keywords: оброблення зображень; безпілотний пристрій